CREATIVE LEARNING APPROACHES: A REVIEW OF THE LITERATURE ON INNOVATION IN THE CLASSROOM - Mukni'ah; Mundir; Mashudi (Indonesian Journal of Education (INJOE), 2025)
Creative learning approaches have been the focus of a recent literature review in an effort to increase innovation in the classroom. This research highlights that the integration of creative methods such as technology, problem-based projects and collaborative activities can strengthen student engagement and improve the quality of learning. Students who engage in these approaches tend to be more motivated and can develop essential skills such as critical thinking and creativity. However, implementing these innovations faces obstacles such as resistance from educators and limited resources. Therefore, comprehensive support from various parties and a change in educational culture are needed to overcome these challenges. Thus, this research confirms that by addressing these constraints, creative learning approaches have great potential to enrich students' learning experiences and outcomes.